Board governance, monetary interest, and closed-end fund performance - Kryzanowski, Lawrence; Mohebshahedin, Mahmood (Journal of Corporate Finance, 2016)
Using a unique, large, and partially hand-collected panel database of U.S. closed-end funds (CEFs) during 1994–2013, we examine relations between board effectiveness and board structure. CEF boards with higher percentages of independent directors are associated with lower expense ratios and different CEF benchmark-adjusted returns, but not with CEF premiums. Thus, independent directors are more effective in monitoring and influencing fund performance measures that are less complex and more directly controllable (fees versus CEF returns). These results are consistent with theoretical and empirical findings in the literature that interested directors can better monitor and control firms with high degrees of information asymmetry, uncertainty, and require specialized knowledge to operate. Our results suggest that CEFs with higher board ownerships are better aligned with shareholders' interests. Ownerships of directors are positively and significantly associated with most variables that are expected to indicate greater value from the monitoring of directors. Using a dynamic panel two-step system generalized method of moments estimator, our results are robust in the presence of endogeneity concerns (reverse causality, unobserved heterogeneity, and simultaneity).